Applying the Consensus Criteria for Traumatic Encephalopathy Syndrome Retrospectively to Case Studies of Boxers from the 20th Century - Grant L. Iverson; Andrew J. Gardner; Rudolph J. Castellani; Alicia Kissinger-Knox (Neurotrauma Reports)
There are no validated diagnostic criteria for traumatic encephalopathy syndrome (TES). During the early and middle 20th century, TES was described as a clinical condition that was experienced by some high-exposure boxers—and it was believed to reflect chronic traumatic brain injury. Consensus criteria for the diagnosis of TES were published in 2021. We applied the consensus criteria for TES retrospectively to cases of chronic brain damage in boxers described in articles published in the 20th century that were obtained from narrative and systematic reviews. The sample included 157 boxers identified in 21 articles published between 1929 and 1999. Two authors reviewed each case description and coded the criteria for TES. For the core clinical features, cognitive impairment was noted in 63.1%, and in 28.7% of cases the person's cognitive functioning appeared to be broadly normal. Neurobehavioral dysregulation was present in 25.5%. One third (34.4%) were identified as progressive, 30.6% were not progressive, and the course could not be clearly determined in 35.0%. In total, 29.9% met the TES consensus criteria, 28.0% did not, and 42.0% had insufficient information to make a diagnostic determination. TES, in the 20th century, was described as a neurological condition, not a psychiatric disorder—and this supports the decision of the 2021 consensus group to remove primary and secondary psychiatric diagnoses from being a core diagnostic feature. Future research is needed to determine whether, or the extent to which, cognitive impairment or neurobehavioral dysregulation described as characterizing TES are associated with chronic traumatic encephalopathy neuropathological change.